Road traffic accidents among primary school children who cycle or walk to school in Kuala Terengganu District, 1996 - Fatimah Muda; Osman Ali (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Road traffic accident constitute a major problem in causing disabilities and deaths in developing and 4eveloped countries. A case control study was conducted in Kuala Terengganu, Terengganu in 1996 among primary school students who cycle or walk to school. The objective of the study is to determine relationship between road traffic accidents and factors such as socio-economic status, distance from school, number of siblings, behavioural problem, knowledge. and attitude of pupil and their parents towards road safety and parents educational status. A total of 140 cases was obtained from 3 urban schools and 3 from rural schools. Cases were matched with control according to age, sex, locality of residence and the manner of going to school. The chi-square test and t -test were used to determine crude association between road traffic accident and risk factor being studied. Multiple logistic regression was used to determine combine affect of main risk factors. Analysis showed that there was no significant association between road traffic accident among primary school children with socio-economic status, number of sibling, behavioural problem, knowledge and attitude of pupil towards road safety, or parental knowledge and educational status. However, there was significant assosiation between road traffic accident and pupils' knowledge regarding road crossing (OR=0.40 95% C.I.0.19,0.85), parental supervision (OR=0.45.95% C.I.0.19, 0.64), and parents who having driving licence (OR=0.99, 95% . 0.856,0.999). In conclusion, road safety education to pupils and parental supervision are key measure in preventing road traffic accidents among primary school children.